MEMAKNAI RADIKALISME DI INDONESIA - Ilham Kurniawan (TA'LIM : Jurnal Studi Pendidikan Islam, 2020)
The absence of standardization of radicalism makes people misunderstand or mistaken and often accuses others of it. This study aims to find out the meaning of radicalism so that people no longer hesitate or wrong in justifying who is radical and interpreting it. This research is a library research (library research) with a qualitative approach. Sources of data obtained in the form of journals, articles, books and relevant scientific work The results of this study explain that radicalism is the understanding or flow that requires social and political change by using violence as a stepping stone to justify their beliefs that are considered true. Forms of radicalism in Indonesia are the perpetrators of the Darul Islam (DI) movement, Hizb ut-Tahrir Indonesia (HTI), Jamaah Ansharut Daulah (JAD), and the Islamic State in Iraq and Syria (ISIS). Visible characteristics or categories of radicalism are as follows: First, takfiri. Second, they want to establish an Islamic state within a country. Third, replace the ideology of a country which is the basis or direction. The anti-radicalism education is carried out by the family, community and education. So that the level of radicalism in Indonesia can decline even completely finished.